2021
DOI: 10.1590/1413-81232021262.38732020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de ansiedade em profissionais da saúde em tempos de COVID-19: revisão sistemática com metanálise

Abstract: Resumo O objetivo deste estudo é identificar a prevalência de ansiedade em profissionais de saúde durante a pandemia da COVID-19. Trata-se de revisão sistemática de estudos publicados em qualquer idioma em 2020. Foi realizada busca nas bases de dados Embase, LILACS e PubMed utilizando os descritores anxiety, COVID-19, health workers, e sinônimos. A estimativa da prevalência geral de ansiedade com intervalo de confiança de 95% foi calculada utilizando o modelo de efeitos aleatórios. Dos 861 registros identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
45

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 90 publications
(324 reference statements)
3
12
0
45
Order By: Relevance
“…However, in the United Kingdom, women in the general population who lived alone and were confined were considered at risk. Being female, a nurse, and belonging to the younger subgroup of workers are factors associated with an increased risk in several studies [63]. Consistent with these findings, women in our study showed a greater loss of psychological wellbeing, PTSD symptoms, and insomnia, which leads us to affirm that gender is a predisposing factor for PTSD risk in our sample.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the United Kingdom, women in the general population who lived alone and were confined were considered at risk. Being female, a nurse, and belonging to the younger subgroup of workers are factors associated with an increased risk in several studies [63]. Consistent with these findings, women in our study showed a greater loss of psychological wellbeing, PTSD symptoms, and insomnia, which leads us to affirm that gender is a predisposing factor for PTSD risk in our sample.…”
Section: Discussionsupporting
confidence: 91%
“…Health professionals working to combat COVID-19 have been more severely affected by psychiatric disorders associated with depression, anxiety, insomnia, stress, and indirect trauma than other occupational groups [139]. In a meta-analysis with 10,267 health professionals from the pandemic front-line, depression was found in 31.5% in this class [136].…”
Section: Complications and Impacts On Mental Healthmentioning
confidence: 99%
“…Procurando formas de minimizar a gravidade do cenário pandêmico, o setor da saúde passou por um processo de adaptação que influenciou o cotidiano dos profissionais da saúde. Após a análise minuciosa dos artigos, tornou-se perceptível que a exaustão causada pela transformação no ambiente trabalho, o aumento da quantidade de pacientes e o crescimento da carga horária tem como consequência não apenas o esgotamento físico como também o mental de profissionais da saúde "evidenciando a necessidade de medidas que visem prevenir este transtorno e que resultem em melhorias na qualidade de vida e na saúde psicológica destes trabalhadores" (Silva, Cobucci, Soares-Rachetti, Lima & Andrade, 2021).…”
Section: Influencia Da Pandemia De Covid-19 Em Profissionais Da Saúdeunclassified